A Review on Aircraft Manufacturing System Design based on Ergonomic Simulation - Veer Zaveri (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The way aircraft are manufactured plays a crucial role in shaping efficiency, costs, and overall quality in the aerospace industry. This study delves into the key principles, methodologies, and technological advancements that define modern aircraft manufacturing system design. It examines both traditional and emerging approaches, such as assembly line optimization, automation, digital twin technology, and Industry 4.0 applications. Additionally, it explores how lean manufacturing, Just-In-Time (JIT) production, and additive manufacturing (3D printing) are helping to improve efficiency and reduce waste. Beyond the technical aspects, this research also highlights some of the major challenges in aircraft manufacturing, including complex supply chains, material selection, precision engineering, and regulatory compliance. By analysing case studies from leading aerospace manufacturers, the study uncovers best practices and the latest trends shaping the industry. Through real-world examples, it provides insights into how companies refine their production processes to meet growing demands for safety, sustainability, and cost-effectiveness. This research adds to the existing body of knowledge by offering an in-depth look at how aircraft manufacturing is evolving. The findings can serve as a valuable resource for aerospace manufacturers, engineers, and policymakers looking to make informed decisions about improving production efficiency, reducing costs, and enhancing aircraft performance. Ultimately, this paper highlights the importance of integrating advanced technologies and lean methodologies to build a more sustainable and efficient future for aircraft manufacturing.